2015
DOI: 10.1542/peds.2015-3232
|View full text |Cite
|
Sign up to set email alerts
|

Global Climate Change and Children’s Health

Jerome A. Paulson,
Samantha Ahdoot,
Carl R. Baum
et al.

Abstract: Rising global temperatures are causing major physical, chemical, and ecological changes in the planet. There is wide consensus among scientific organizations and climatologists that these broad effects, known as “climate change,” are the result of contemporary human activity. Climate change poses threats to human health, safety, and security, and children are uniquely vulnerable to these threats. The effects of climate change on child health include: physical and psychological sequelae of weather disasters; in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…As a group, children in particular will suffer from climate change. They are both physically and psychologically vulnerable to abnormal weather disasters that will cause food, water, and nutrient insecurity in vulnerable regions [25,26]. Children are also inherently more sensitive than adults to sudden weather changes, since they cannot adapt to rainstorms, snowstorms, heat waves, and other extreme climate-related exposures the same way that adults do [25].…”
Section: The Consequences Of the Anthropocenmentioning
confidence: 99%
“…As a group, children in particular will suffer from climate change. They are both physically and psychologically vulnerable to abnormal weather disasters that will cause food, water, and nutrient insecurity in vulnerable regions [25,26]. Children are also inherently more sensitive than adults to sudden weather changes, since they cannot adapt to rainstorms, snowstorms, heat waves, and other extreme climate-related exposures the same way that adults do [25].…”
Section: The Consequences Of the Anthropocenmentioning
confidence: 99%
“…( Schachtel and Boos, 2019 ) Children’s full dependency on adult caregivers compounds the challenges inherent in avoiding deleterious environmental surroundings; this is mirrored in the geriatric population. ( Ahdoot and Pacheco, 2015 ) The elderly are also at elevated risk for contracting dermatologic disease due to the natural weakening of the immune system with age, which includes reduced resiliency and functionality of the skin’s cutaneous barrier. ( Humbert et al, 2016 ); ( Quan and Fisher, 2015 )…”
Section: Aad Position Statement and Vulnerable Populationsmentioning
confidence: 99%
“…People with preexisting mental illness are at increased risk following weatherrelated events (Trombley et al 2017), as are youth (Paulson et al 2015;Orengo-Aguayo et al 2019). Likewise, climate "surprises" (see Section 2) such as flooding (Lamond et al 2015), wildfires, or storms have been shown to impact mental health.…”
Section: Mental Health Concernsmentioning
confidence: 99%